Study of B(0)->pi(0)pi(0), B(+/-)->pi(+/-)pi(0), and B(+/-)-> K(+/-)pi(0) decays, and isospin analysis of B ->pi pi decays - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2007)
We present updated measurements of the branching fractions and CP asymmetries for B0→π0π0, B±→π±π0, and B±→K±π0. Based on a sample of 383×106 Υ(4S)→BB̄ decays collected by the BABAR detector at the PEP-II asymmetric-energy B factory at SLAC, we measure B(B0→π0π0)=(1. 47±0.25±0.12)×10-6, B(B±→π±π0)=(5. 02±0.46±0.29)×10-6, and B(B±→K±π0)= (13.6±0.6±0.7)×10-6. We also measure the CP asymmetries Cπ0π0=-0.49±0.35±0.05, Aπ±π0=0.03±0. 08±0.01, and AK±π0=0.030±0.039±0.010. Finally, we present bounds on the Cabibbo-Kobayashi-Maskawa angle α using isospin relations. © 2007 The American Physical Society.